Interpersonal Communication Style of Generation Z: The Role of Social Media in Relationship Patterns, Trust, and Self‑Disclosure - Yuliana, Yuliana; Irma, Ade (ISTIFHAM, 2026)
This study examines how social media influences interpersonal communication among Generation Z by focusing on three fundamental dimensions: digital relational patterns, trust formation, and self-disclosure mechanisms. Utilising a qualitative phenomenological approach, data were collected through in-depth interviews with eight informants aged 18–27 who actively utilise social media for interpersonal communication. The findings reveal that digital relationships develop rapidly through intense communication rhythms, yet remain fluctuating and highly contingent upon the continuity of messaging. Trust in digital interactions is established through the consistency between an individual’s online persona and offline behaviour, positioning authenticity as a crucial indicator of interpersonal credibility. Conversely, self-disclosure occurs selectively through audience-control features such as close friends, private messages, or secondary accounts, enabling users to express themselves in a sense of emotional security. The study concludes that social media functions not only as a communication tool but also as a social space that influences the dynamics of closeness, trust, and self-expression among Generation Z. These findings integrate Social Information Processing Theory, Social Penetration Theory, Impression Management, Warranting Theory, and the Online Disinhibition Effect to provide a more comprehensive understanding of digital interpersonal relationships among young generations.